Avaliação dos níveis de MP 2.5 em microambientes : um alerta para a cidade de Porto Alegre, RS - Rosa, Michele dos Santos Gomes da (2015)
Objective: To describe the levels of pollution in public schools from the city of Porto Alegre. Methods: Thus, the aim of this work was to investigate the relationship between weather conditions an air quality of some public schools in Porto Alegre. Indoor and outdoor particulate matter concentrations were measured and analysed throughout the four seasons. Mobile devices were used to measure particulate matter concentrations in nive microenvironments near schools and in the routes used by students. Temperature, humidity and wind were also measured. Results: The particulate matter concentrations in the nine microenvironmets were similar and mostly higher than the tolerated level recommended by the World Health Organization (WHO). Conclusion: It was observed that only in the autumn season the particulate matter concentrations remained close to the exposure levels recommended by WHO for 24 hours.